EXPLORING READING SPEED USED BY EFL STUDENTS - Abdul Rohman (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
Reading speed is the solution to today's pressing challenge for students, who must complete more work or assignments in less time. Reading speed is becoming increasingly important as technology advances, causing readers to require a deeper understanding of the information provided. Furthermore, reading speed is combined with several techniques or strategies to help students read quickly with limited time. This study was conducted in Eight Semesters of the English Department. To find the result in this study, the researcher used interviews and documentation as instruments to collect the data. The subjects in this study are fourteen which are 13 students and one lecturer. The findings showed the students were had various types of reading strategies used in reading speed, and a student may use one or more of them. Skimming, scanning, and silent reading are the most common strategies they employ. However, in terms of reading speed, the students preferred silent reading. These techniques aid in their reading comprehension. In other words, the internal factors students’ equally contributed to the lecturers' problem during teaching reading lessons.